China-Indonesia People-to-people exchanges in the New Era: Mechanisms, Current Situation and Challenges - Xinyue Wei; Chen Sun; Zhangfeng Zhao (Universitas Negeri Surabaya, 2024)
People-to-people exchanges are the public opinion basis for China and Indonesia to carry outcooperation in various fields, and are also an important cornerstone for the two countries to build acommunity with a shared future. Bilateral and multilateral high-level dialogue mechanisms provide aneffective platform for people-to-people exchanges. The overall improvement of China-Indonesia relations,deepening of political mutual trust and close economic cooperation have laid a realistic foundation forbilateral people-to-people exchanges. In the new era, cooperation of bilateral people-to-people exchangeshave achieved fruitful results, mainly in education, science and technology, sports, youth, tourism anddigital fields. At present, the China-Indonesia people-to-people exchanges’ mechanism continues to developand the areas of cooperation continue to expand, forming a pattern of multi-level exchanges between GOand NGO. At the same time, the deepening of people-to-people exchanges still faces challenges such asIndonesia’s internal factors, insufficient people’s exchanges, and the Indo-Pacific geopolitical structure.